Calculation of plate-beam systems by method of boundary elements - Surianinov, Mykola; Shyliaiev, Oleksii (International Journal of Engineering and Technology, 2018)
The approach to calculation of plate-beam systems by numerical and analytical method of boundary elements is proposed. The method consists in construction in analytical way a fundamental system of solutions, the Greenâ€™s function and external load vector for the problem under consideration. Small system of linear algebraic equations to be solved numerically is constructed to take into account the boundary conditions or contact conditions between separate modules.The series of plate-beam system calculations by methods of boundary elements and finite elements at different geometric parameters of plate was performed to assess the limits of applicability of developed theory. The comparison of 45 variants calculations by both methods is shown.Â Â